Dormia basket impacted during ERCP, resolved by laparoscopic bile duct approach: Case report - Vargas Ávila, Arcenio Luis (Int J Surg Case Rep, 2021)
INTRODUCTION: Endoscopic retrograde cholangiopancreatography (ERCP) is the method of choice for treating and removing common bile duct (CBD) stones with high success rates. Among the adverse effects, impaction of the Dormia basket when removing the stones is an unusual complication. CASE PRESENTATION: Two cases of choledocholithiasis with endoscopic treatment by ERCP and Dormia basket impaction, resolved by a laparoscopic approach to the bile duct. DISCUSSION: Laparoscopic common bile duct exploration (LCBDE) has been developed as a technique to treat choledocholithiasis and simultaneously vesicular lithiasis by laparoscopy. LCBDE can be by means of a transcystic approach or by choledochotomy. The success of the treatment depends on surgical experience and the availability of adequate equipment, with high effectiveness to eliminate CBD stones and a success rate greater than 95%, it is equally effective for the resolution of adverse events during ERCP. CONCLUSION: LCBDE provides an alternative therapy where there is no other type of treatment for the resolution of complications of ERCP. It is a safe, effective and reliable technique with high success rates, which offers the benefits of a minimally invasive approach.